2017
DOI: 10.1186/s11671-017-2330-3
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Mechanism and Improved Endurance in HfO2-Based RRAM with Nitridation Treatment

Abstract: A nitridation treatment technology with a urea/ammonia complex nitrogen source improved resistive switching property in HfO2-based resistive random access memory (RRAM). The nitridation treatment produced a high performance and reliable device which results in superior endurance (more than 109 cycles) and a self-compliance effect. Thus, the current conduction mechanism changed due to defect passivation by nitrogen atoms in the HfO2 thin film. At a high resistance state (HRS), it transferred to Schottky emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 16 publications
4
31
0
Order By: Relevance
“…Their electrical behavior is largely influenced by the choice of top and bottom electrodes (TE and BE respectively), the presence of oxygen vacancy-rich interfacial layers, or the quality of the metal-oxide layer. Various techniques can be used to deposit HfO 2 layers, including the atomic layer deposition (ALD) 19,25,2729 , pulsed laser deposition 30 , metal organic and chemical vapor deposition (MOCVD or CVD) 31 , physical deposition by magnetron sputtering 20,3234 and more recently, sol-gel spin-coating method 3544 . The ALD, CVD and sputtering techniques all provide a relatively good control over the deposited material properties and high yield.…”
Section: Introductionmentioning
confidence: 99%
“…Their electrical behavior is largely influenced by the choice of top and bottom electrodes (TE and BE respectively), the presence of oxygen vacancy-rich interfacial layers, or the quality of the metal-oxide layer. Various techniques can be used to deposit HfO 2 layers, including the atomic layer deposition (ALD) 19,25,2729 , pulsed laser deposition 30 , metal organic and chemical vapor deposition (MOCVD or CVD) 31 , physical deposition by magnetron sputtering 20,3234 and more recently, sol-gel spin-coating method 3544 . The ALD, CVD and sputtering techniques all provide a relatively good control over the deposited material properties and high yield.…”
Section: Introductionmentioning
confidence: 99%
“…With baking time increasing, a high-frequency collision accompanied by the increased generation and recombination rate occur. In this case, high migration rate of Vos induces a large possibility of forming clusters [6], as shown in Fig. 8d.…”
Section: Physical Mechanismsmentioning
confidence: 83%
“…However, the retention behavior of the intermediate conductance states was not considered, which is precisely the most noteworthy part. As for the endurance, current researches on binary switching have involved several aspects, including device structure and material optimization [6], correction techniques [7], programming voltage schemes [8], [9], and physical mechanism of endurance failure [10], [11]. But the analysis of endurance degradation of analog RRAM has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…We note that similar considerations relating to material stability under repeated operation have also been the a b c e d subject of significant work in developing this class of materials for non-volatile memory applications with high cycling endurance. For instance, studies have shown that endurance can be improved via using alloy electrodes like Ag-Te [38], Ag-Cu [39], inserting Ag diffusion barrier layer [40], area scaling of the device switching region [41], using host materials with stronger chemical bonding among its components [42], nitridation [43]. We anticipate that resistance to such microstructural degradation for the case of the ARS may similarly be achieved by designing optimized electrode, switching structures, adjusting resistor area, new host matrix and electrode materials, and the introduction of solute additives that can retard diffusive processes that exacerbate microstructural fatigue.…”
Section: Discussionmentioning
confidence: 99%